Amyloid-like p53 as prognostic biomarker in serous ovarian cancer—a study of the OVCAD consortium - Heinzl, Nicole; Maritschnegg, Elisabeth; Koziel, Katarzyna; Schilhart-Wallisch, Christine; Heinze, Georg; Yang, Wei-Lei; Bast, Robert C.; Sehouli, Jalid; Braicu, Elena I.; Vergote, Ignace; Van Gorp, Toon; Mahner, Sven; et al. (Oncogene, 2023)
TP53 is the most commonly mutated gene in cancer and has been shown to form amyloid-like aggregates, similar to key proteins in neurodegenerative diseases. Nonetheless, the clinical implications of p53 aggregation remain unclear. Here, we investigated the presence and clinical relevance of p53 aggregates in serous ovarian cancer (OC). Using the p53-Seprion-ELISA, p53 aggregates were detected in 46 out of 81 patients, with a detection rate of 84.3% in patients with missense mutations. High p53 aggregation was associated with prolonged progression-free survival. We found associations of overall survival with p53 aggregates, but they did not reach statistical significance. Interestingly, p53 aggregation was significantly associated with elevated levels of p53 autoantibodies and increased apoptosis, suggesting that high levels of p53 aggregates may trigger an immune response and/or exert a cytotoxic effect. To conclude, for the first time, we demonstrated that p53 aggregates are an independent prognostic marker in serous OC. P53-targeted therapies based on the amount of these aggregates may improve the patient’s prognosis.